2019
DOI: 10.1021/acs.langmuir.8b03532
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Shock Synthesis of Metal Nanoclusters within On-the-Fly Graphene Particles

Abstract: Metal nanoclusters (1–10 nm) have drawn great attention because of their potential applications including energy storage, catalysis, nanomedicine, and electronic devices. However, manufacturing ultrasmall metal nanoparticles at high concentrations in an unaggregated state is not a solved problem. Here, we report an aerosol-based thermal shock technique for in situ synthesis of well-dispersed metal nanoclusters in on-the-fly graphene aerosols. A rapid thermal shock to the graphene aerosol has been used to nucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…This saturation ratio change is mainly affected by four primary processes: (a) generation of Pt atoms from thermal decomposition of H 2 PtCl 6 , (b) consumption of Pt atoms due to nucleus formation, (c) evaporation of Pt atoms from the surface of the stable nuclei, and (d) consumption of vapor phase Pt atoms due to Pt condensation onto the surface of the existing nuclei. These processes can be well described by the moment model as follows: 17,18…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This saturation ratio change is mainly affected by four primary processes: (a) generation of Pt atoms from thermal decomposition of H 2 PtCl 6 , (b) consumption of Pt atoms due to nucleus formation, (c) evaporation of Pt atoms from the surface of the stable nuclei, and (d) consumption of vapor phase Pt atoms due to Pt condensation onto the surface of the existing nuclei. These processes can be well described by the moment model as follows: 17,18…”
Section: Resultsmentioning
confidence: 99%
“…This saturation ratio change is mainly affected by four primary processes: (a) generation of Pt atoms from thermal decomposition of H 2 PtCl 6 , (b) consumption of Pt atoms due to nucleus formation, (c) evaporation of Pt atoms from the surface of the stable nuclei, and (d) consumption of vapor phase Pt atoms due to Pt condensation onto the surface of the existing nuclei. These processes can be well described by the moment model as follows: , Here, R H is the reaction rate of metal salt precursor decomposition to zerovalent metal atoms, and A is the total surface area of all the nuclei in the reaction volume; both R H and A are time-dependent variables. k * is the number of monomers in a single particle with a critical radius r c , and n s is the monomer concentration at saturation condition.…”
Section: Resultsmentioning
confidence: 99%
“…15 (iv) Pyrolysis-based procedures can be used to produce welldefined metallic nanoclusters in a carbon media/substrate, with activation temperatures ranging from 600 to 900 °C. 16,17 Therefore, we can expect the coexistence of two fundamental mechanisms, both in synthesis and application, namely, (i) the temperature will change the nanocluster morphology and (ii) the morphological change will affect the observed properties of the system. However, we do not yet know how these morphological changes modulate the properties observed experimentally in these materials.…”
Section: Introductionmentioning
confidence: 99%
“…33−35 To perform CTS via Joule heating, the carbon substrate requires sufficient electrical conductivity to generate high temperatures at ultrafast heating rates. Studies have shown CTS being applied to commercial and synthetic carbon substrates, such as a CO 2 -activated carbon nanofiber, 33,36 aligned electrospun carbon nanofiber, 37 carbon fiber cloth, 30 graphene, 38,39 and rGO. 40,41 These freestanding carbon films are binderless to minimize resistive heating loss across the carbon electrode during CTS; an example of such a film that has yet to be studied with CTS treatment includes GO as a result of its poor electrical conductivity.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Recently, researchers have demonstrated numerous benefits of CTS, including the ability to deposit nanoparticles onto carbon substrates with precise control of the nanoparticle density, size, and composition (e.g., nanoparticles comprising up to eight elemental constituents). To perform CTS via Joule heating, the carbon substrate requires sufficient electrical conductivity to generate high temperatures at ultrafast heating rates. Studies have shown CTS being applied to commercial and synthetic carbon substrates, such as a CO 2 -activated carbon nanofiber, , aligned electrospun carbon nanofiber, carbon fiber cloth, graphene, , and rGO. , These free-standing carbon films are binderless to minimize resistive heating loss across the carbon electrode during CTS; an example of such a film that has yet to be studied with CTS treatment includes GO as a result of its poor electrical conductivity. Of note, a pre-annealing step is typically performed at a high temperature under an inert atmosphere to slightly improve the conductivity of GO, which is then subsequently subjected to Joule heating to produce rGO. , In this manner, where Joule heating is carried out on a longer time scale, rGO has shown to exhibit promising electrochemical performance. , The low electrical conductivity of GO (∼10 –5 S cm –1 ) limits itself to any rapid Joule heating-induced reduction; thus, preparing a composite with an electrically conductive additive, like CNTs (up to 10 6 –10 7 S cm –1 ), is necessary and unique to this work.…”
Section: Introductionmentioning
confidence: 99%